A qualitative study illustrating factors that enable and constrain academic advising practices in a Global South context - Versfeld, Jessica; Mapaling, Curwyn (Frontiers in Education, 2024)
Considering South Africa's diverse student population, historical injustices, and major socioeconomic inequalities, academic advising assumes a pivotal role in the South African higher education landscape. However, the existing body of research supporting its practices is notably deficient. Consequently, this article employs a qualitative methodology, specifically semistructured in-depth interviews, to delve into the landscape of academic advising in South African universities by interviewing four Engineering, Built Environment, and Information Technology (EBIT) academic advisors. The study aims to explore the unique challenges and opportunities faced by academic advisors within engineering departments. Key findings reveal that advisors face challenges such as limited resources and institutional support, while opportunities include fostering student resilience and academic success. Employing a socioecological lens, this crucial study endeavours to explore the factors that enable and constrain best practices in academic advising in South Africa. As part of the Global South, South Africa shares many socio-economic and educational challenges with other countries in this region. This study's findings on academic advising practices offer insights that may be relevant to similar contexts across the Global South. By adopting this lens, this study aims to illuminate the mechanisms that empower the academic advising community in South Africa to deliver more effective interventions to students. By strategically situating these factors within the socio-ecological framework, this study seeks to provide a comprehensive understanding of the interconnected influences that contribute to the efficacy and challenges faced by academic advisors in an engineering department.